Study on AC Over-Current Characteristics With Physical Properties of the Outer Layer of GdBa2Cu3O7-x Thin-Film-Type Superconducting Wire Having Composite Structure Using RF Sputtering Deposition Method - Du, Ho-Ik; Jeong, Hyeon-Gi; Ban, Sang-Jae; Yang, Sung-Chae (IEEE transactions on applied superconductivity, 2022)
Superconducting application technology, which is an eco-friendly core technology in the field of electric power and energy transport in the future industry, can be developed starting with the improvement of the performance of superconducting wires with excellent critical characteristics. A thin-film-type superconducting wire, which is created in the form of a multi-layered thin film, is a key element in superconducting power devices. Various surface treatment technologies can be applied to the stabilization layer among the multiple thin-film layers of thin-film-type superconducting wire, and a surface treatment technology using plasma can also be used. Surface treatment technology using plasma has already been applied to various materials as a means to improve the critical properties of materials. Based on these premises, this study sought to change the physical properties of thin-film-type superconducting wire by applying the plasma surface treatment technology to the stabilization layer of GdBa 2 Cu 3 O 7-X thin-film-type superconducting wire, a core material for superconducting power devices. The changed electrical conduction characteristics are analyzed by measuring the critical currents of 8 specimens, as well as AC overcurrent, which is the main subject of this study. The findings of the test indicate that the electrical properties of the thin-film-type superconducting wire depend on the physical properties of the additionally deposited material. Accordingly, the electrical performance of the thin-film-type superconducting wire also varies. In addition, the plasma surface treatment technology is deemed suitable for the change in the electrical performance of thin-film-type superconducting wire.